Latest Innovations in Teaching English Using Virtual Reality Technologies - Pazilov Abdushohit Abduvaeitovich (Genius Journals, 2022)
This paper presents an analysis of innovative solutions using virtual reality for the practice of foreign languages on the example of the English language. There are two types of software applicable in the framework of the educational process in schools and universities: specialized and related developments. The results of the analysis demonstrate that virtual reality as an educational technology has potential, but is still at the initial stage of its development, and existing applications need methodological improvements and additional research on effectiveness.
Keywords: Virtual reality; information technology; pedagogy; educational technology